Preferensi Santri Putra pada Bmt Sunan Drajat Paciran di Pondok Pesantren Sunan Drajat Lamongan - Fatkhur Rouf; Musbikhin; Ahmad Afan Zaini (Al-Muzdahir : Jurnal Ekonomi Syariah, 2019)
BMT Sunan Drajat Paciran is one of the BMT that was established on 07 November 2018. BMT Sunan Drajat is a Sharia based microfinance institution where the main target is the Paciran community and Sunan Drajat Lamongan Students. And the purpose of establishing BMT Sunan Drajat Paciran is to help the community in increasing their opinion, and also to save the community from the snares of moneylenders. In addition, BMT Sunan Drajat Paciran also has another purpose, namely to accomodate, serve students in financial matters such as lending and borrowing, saving, and others. This study aims to answer, describe, and analyze the formulation of the problem, namely how the preferences of male student at BMT Sunan Drajat. The research is quantitative research. By using the Chi Square test analysis method and the research instrunent used to collect data is by using interviews, questionnaires, and documentation. The results of this study are 1) in the knowledge variable there is a calculated Chi Square value is equal to 10, 967. Because the value of Chi Square < 13,362, it can be concluded that H0 is accepted and Ha is rejected. Thus it can be interpreted that male students do not have a good preference for BMT Sunan Drajat. 2) in the professionalisme variable there is a calculated Chi Square value of 14,225. In the access variable there is a calculated Chi Square value of 18,909. In the facility variable, the calculated Chi Square value is 14,474. Becauseall Chi Square Values > 13,362, it can be concluded that H0 is rejected and Ha is accepted. Thus it can be interpreted that male students have a good preference for BMT Sunan Drajat.